The Effect of Project-Based Learning on Students’ Speaking Skill: Evidence from Pangkajene Regency - Khaerunnisa; Muhammad Tahir; Munir (International Journal of Language, Education, and Literature, 2026)
This study investigates the effectiveness of the Project-Based Learning (PJBL) method in enhancing students’ speaking skills at SMPN 2 Balocci, Pangkajene Regency. The research is grounded in Thomas’s (2000) framework of PJBL, which emphasizes learner-centered instruction through authentic, meaningful projects that require students to actively engage, collaborate, and produce tangible outcomes. It is also supported by Brown’s (2004) theory of speaking skills, which highlights three essential components—fluency, accuracy, and comprehensibility—as fundamental aspects of oral communication competence. The combination of these frameworks provided both theoretical and pedagogical foundations for this study. A pre-experimental research design with a one-group pre-test and post-test model was employed. The sample consisted of 73 purposively selected students. Data were collected through an individual speaking test divided into three sections: introduction, monologue, and interactive discussion. Students’ performances were assessed using the JACOB (1980) speaking rubric, which evaluates accuracy, fluency, and comprehensibility as indicators of communicative ability. The findings revealed a significant improvement in students’ speaking performance following the implementation of the PJBL method. The mean score increased substantially from the pre-test to the post-test, indicating notable progress in students’ oral proficiency. Results from the paired sample t-test confirmed that the difference between pre-test and post-test scores was statistically significant at the 0.05 level (p < 0.05). This demonstrates that the PJBL method effectively contributes to the development of students’ speaking skills. In conclusion, the Project-Based Learning method not only improved students’ ability to speak English more fluently, accurately, and comprehensibly but also fostered motivation, creativity, and collaboration in the classroom. The findings suggest that PJBL is a promising instructional approach for English language learning, particularly in contexts where communicative competence and student engagement are prioritized.